1995
DOI: 10.1097/00000542-199507000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Platelet Aggregation by Inhaled Nitric Oxide in Patients with Acute Respiratory Distress Syndrome

Abstract: In patients with ARDS and without preexisting coagulation disorders, the beneficial effects of inhaled nitric oxide on arterial oxygenation and pulmonary circulation are associated with a significant inhibition of platelet aggregation. This antithrombotic effect is not associated with a significant prolongation of the bleeding time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
4
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(49 citation statements)
references
References 22 publications
0
43
4
2
Order By: Relevance
“…19,25,26 In this study, iNO therapy had a significant effect on BBB dysfunction as measured by EB extravasation, so the shown reduction of brain water content is most probably because of a combination of reduction of vasogenic and cytotoxic edema formation. Furthermore, NO inhalation has been shown to exert anti-platelet activity [38][39][40] and to act anti-inflammatorily. 29,41 We previously showed that microthrombus formation occurs in our model of murine CCI and further deteriorates CBF; 42 in the same study leukocyte-platelet aggregates were detected in cerebral venules.…”
Section: Discussionmentioning
confidence: 99%
“…19,25,26 In this study, iNO therapy had a significant effect on BBB dysfunction as measured by EB extravasation, so the shown reduction of brain water content is most probably because of a combination of reduction of vasogenic and cytotoxic edema formation. Furthermore, NO inhalation has been shown to exert anti-platelet activity [38][39][40] and to act anti-inflammatorily. 29,41 We previously showed that microthrombus formation occurs in our model of murine CCI and further deteriorates CBF; 42 in the same study leukocyte-platelet aggregates were detected in cerebral venules.…”
Section: Discussionmentioning
confidence: 99%
“…Human SMCs were dyed by DiI before seeding onto each film in 48-well plates at a density of 2×10 4 per well with 200 μmol L 1 GSNO and 200 μmol L 1 GSH for 2 h at 37°C. The adhered cells were fixed in 4% paraformaldehyde for 10 min and observed with inverted fluorescence microscope.…”
Section: Smcs Adhesionmentioning
confidence: 99%
“…5×10 4 SMCs with 200 μmol L 1 GSNO and 200 μmol L 1 GSH were seeded onto each film and cultured for 4 h at 37°C. The cells were then stained with FITC-labeled phalloidin and observed under confocal laser scanning microscopy (CLSM; TCS SP5; Leica, Germany), or fixed in 2.5% glutaraldehyde overnight and dehydrated in gradient ethanol for SEM observation.…”
Section: Smcs Spreadingmentioning
confidence: 99%
“…iNO is associated with increased bleeding time and inhibition of platelet aggregation in adults. 29,30 A Cochrane review of randomized studies of iNO in the near-term infants did not find an association between the use of iNO and bleeding events. 18 …”
Section: Left Ventricular Dysfunctionmentioning
confidence: 99%